Effects of Glycyrrhiza Polysaccharides on Chickens' Intestinal Health and Homeostasis - Wu, Yu; Wu, Chenyang; Che, Yanyun; Zhang, Tao; Dai, Chen; Nguyễn, Audrey D.; Duan, Kun; Huang, Yanyu; Li, Nannan; Zhou, Hui; Wan, Xin; Wang, Yuedi; et al. (Frontiers in Veterinary Science, 2022)
The overuse of antibiotics in poultry farming causes the accumulation of drug residue in animals' bodies and the occurrence of antibiotic-resistant bacteria, which not only compromise animals' health but ultimately endanger human health. Thus, there is an urgent need for a novel poultry feed additive to substitute for excessive antibiotics. Glycyrrhiza polysaccharides (GPS) derived from Chinese licorice have shown promising immunomodulatory effects in previous studies. The present study investigated the pharmacological effects of GPS on poultry intestines to assess whether it can be used as a feed additive. The results show that GPS can increase production of sIgA, promote the secretion activity of goblet cells, alter the gut microbial composition and lead to changes in short-chain fatty acids. GPS also elevated both Th1 and Th2 immune responses by facilitating the expression of IL-2, IL-4, IL-1β, and IFN-γ while increasing the proportion of both CD4+ and CD8+ cells in the intestine. Moreover, the results of 16S rRNA gene sequencing showed that GPS could significantly change intestinal microbiota composition in the intestine, evidenced by the increased proportion of Bacteroides, Butyricicoccus and Eisenbergiella, as well as a decreased portion of Erysipelatoclostridium, leading to a healthier intestinal microbiota composition for the host. Taken together, it can be concluded that GPS is safe to use as a novel feed additive that can be used as an alternative to prophylactic antibiotics in poultry feeding.